VD_FINDINFO Jug / 2015 / 44 vom 9. Mai 2014 - VD Tribunal cantonal (2014)
DROIT PÉNAL DES MINEURS, CONSTATATION DES FAITS, FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 25 DPMin, 35 DPMin, 10 CPP (CH)